MODEL MAHATMA GANDHI DALAM DUNIA POLITIK Sebuah Eksposisi Praktis di Era Kontemporer - I Gede Suwantana (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2013)
Abstract Mahatma Gandhi has been a master for himself. Master is meant in the sense that he has mastered all the lust, greed, violence, anger and other negative forms within. People who have been releasing these negative tendencies will have a special quality in it radiates purity, without tendentious and interests to be achieved fully for the common good. Gandhi demonstrated that to achieve this goal, using any means used must be in accordance with morality. By relying on the truth, Gandhi had his political career with courage. Tools to achieve it is Ahimsa, so that Satyagraha struggle could walk perfectly. Key Words: Ahimsa, satyagraha, satya,